2016
DOI: 10.1007/s11060-016-2276-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity profile of bevacizumab in the UK Neurofibromatosis type 2 cohort

Abstract: Bevacizumab is considered an established part of the treatment strategies available for schwannomas in patients with Neurofibromatosis Type 2(NF2). In the UK, it is available through NHS National Specialized Commissioning to NF2 patients with a rapidly growing target schwannoma. Regrowth of the tumour on suspension of treatment is often observed resulting in prolonged periods of exposure to bevacizumab to control the disease. Hypertension and proteinuria are common events with bevacizumab use and there are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…However, the long‐term effects of the medication, which appears to require continued dosing to keep the papilloma under control, is not yet known, and there is little information about the best protocol to use because of the lack of clinical trials. Some insight might come from the use of systemic bevacizumab as a maintenance therapy for neurofibromatosis 2, where it is used as a nonsurgical modality for skull base schwannomas . More data may come from the treatment of Rendu‐Osler‐Weber disease, where lower doses of systemic bevacizumab are currently being used to treat refractory bleeding .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the long‐term effects of the medication, which appears to require continued dosing to keep the papilloma under control, is not yet known, and there is little information about the best protocol to use because of the lack of clinical trials. Some insight might come from the use of systemic bevacizumab as a maintenance therapy for neurofibromatosis 2, where it is used as a nonsurgical modality for skull base schwannomas . More data may come from the treatment of Rendu‐Osler‐Weber disease, where lower doses of systemic bevacizumab are currently being used to treat refractory bleeding .…”
Section: Discussionmentioning
confidence: 99%
“…Some insight might come from the use of systemic bevacizumab as a maintenance therapy for neurofibromatosis 2, where it is used as a nonsurgical modality for skull base schwannomas. 10 More data may come from the treatment of Rendu-Osler-Weber disease, where lower doses of systemic bevacizumab are currently being used to treat refractory bleeding. 11,12 Even with the limitations of this study, we report the use of systemic bevacizumab in two children without major complications and with a positive effect on respiratory symptoms during a follow-up of 4 years and 19 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…23,24,[26][27][28][29] Those affected mildly, although suffering hearing loss, often live a full lifespan, work and reproduce. 34,35 Other agents including Everolimus have been tried but evidence on efficacy and safety is limited. 30 Management aims to maintain function and slow progression 3,31,32 but is complicated due to fear of radiation induced malignancy, 33 neurosurgical morbidity and Bevacizumab induced hypertension and proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…30 Management aims to maintain function and slow progression 3,31,32 but is complicated due to fear of radiation induced malignancy, 33 neurosurgical morbidity and Bevacizumab induced hypertension and proteinuria. 34,35 Other agents including Everolimus have been tried but evidence on efficacy and safety is limited. 36 Natural history NF2 data utilising current management is important, to inform management options.…”
mentioning
confidence: 99%
“…Recent reports showed that BEV decreased the cysts' size of vestibular schwannoma, a representative tumor of extra-axial brain tumor, in neurofibromatosis type 2 patients. 7,8 However, there has been no report about BEV effect against cysts of intra-axial brain tumor including high grade glioma. In this study, we focused on the cystic components of intra-axial brain tumors.…”
Section: Introductionmentioning
confidence: 99%